(untitled) (Research, Society and Development, 2020)
Objective: To perform a literature review on unspecified speech motor delay, how it is evaluated and how it differs from other speech motor disorders. Research strategy: This is an integrative literature review. SciELO, PubMed, Medine and Scopus databases were searched in November 2019. For the four databases the following constructs and descriptors were used: “motor speech disorders” OR “childhood apraxia of speech” OR “childhood apraxia of speech cas” OR “developmental dyspraxia” OR “speech sound disorder” AND “speech motor control”, besides the use of two filters: subjects up to 18 years old and humans. Selection criteria: Articles published in Portuguese, English or Spanish were included, whether or not from open access journals. Articles that were not related to unspecified speech motor delay and literature review studies were excluded. Results: 56 articles were found in the databases, 33 from Scopus, 19 from PubMed, 3 from SciElo and 1 from Medline. After analysis and selection by inclusion criteria, 14 studies were selected. After the full reading of the articles, 8 studies were excluded because they did not answer the guiding questions of the research, resulting in a n of 6 studies. Conclusion: Many children with significant speech delay are misdiagnosed, with DMS-NOS being the most prevalent childhood disorder.